1985
DOI: 10.1039/f19858101357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of support acidity and Ce3+ additives on the reactivity of nickel particles highly dispersed on various oxide supports

Abstract: Important modifications to the reactivity of metallic nickel highly dispersed on various oxide supports have been observed. These vary according to the acidity of the support and the presence of Ce3+ additives. The loss or attenuation of hydrogen chemisorption properties and catalytic activity in butane hydrogenolysis seems to be correlated to the acidity of the support, which leads to a total or partial coverage of the metallic surface during the reduction process by hydrogen, which remains strongly chemisorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The enhanced catalytic activity, except for 5-2.5 Nice/X, and the significant increase in the selectivity to higher molecular weight hydrocarbons were evident with the presence of cerium additives. The results are in agreement with those reported by Sauvion et al [5] for ion-exchanged catalysts. In the present studies, the catalytic activities were strongly dependent on the concentration of Ce3+ cations or the Ce3+-to-N?+ ratio.…”
Section: Catalytic Activity and Selectivity For Carbon Monoxide Hydrogenationsupporting
confidence: 93%
See 1 more Smart Citation
“…The enhanced catalytic activity, except for 5-2.5 Nice/X, and the significant increase in the selectivity to higher molecular weight hydrocarbons were evident with the presence of cerium additives. The results are in agreement with those reported by Sauvion et al [5] for ion-exchanged catalysts. In the present studies, the catalytic activities were strongly dependent on the concentration of Ce3+ cations or the Ce3+-to-N?+ ratio.…”
Section: Catalytic Activity and Selectivity For Carbon Monoxide Hydrogenationsupporting
confidence: 93%
“…Several experimental results have shown that the addition of second metal ions to oxide-supported metal catalysts can cause a synergistic effect in addition to having a dramatic influence on the surface metal dispersion and on the catalytic properties. Various mechanisms have been proposed, such as the formation of bimetallic alloys [ 11, dopant-induced metal-support interactions [ 21, the presence of chemical anchors [ 3,4] and strong metal-support interactions (SMSI) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multivalent exchangeable ions have been reported to significantly affect the size and the electronic structure of transition metal species in zeolite cages. Such ions can exert a “chemical” anchoring effect on Pt particles, preventing their aggregation to larger clusters. , Electronic structure effects on metal clusters in zeolites have been identified for Ni and Rh. , …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, not only the dilution effect of alumina on the support but also the strong alumina pillar-phosphate interaction might be responsible for the lower interaction between nickel particles and pillared phosphates. It has been demonstrated that a change in the electron density of the metal can significantly modify chemisorption and catalytic properties (20). Furthermore, nickel catalysts supported on fluorinated alumina pillared α-zirconium phosphates could be easily regenerated by oxidation in air and further reduction under the same conditions or simply by treatment with a H 2 /He flow at 773 K (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the low reducibility observed in nickel-zeolite systems may be accounted for in terms of strong metal-support interactions as well (13,14). Several strategies have been envisaged to overcome this inconvenience, for instance, calcining the alumina support at T > 873 K before contacting with the Ni 2+ salt (15), and adding alkaline or transition metal ions (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%